2019
DOI: 10.3390/atmos10090512
|View full text |Cite
|
Sign up to set email alerts
|

Experience from Integrated Air Quality Management in the Mexico City Metropolitan Area and Singapore

Abstract: More than half of the world’s population now lives in cities as a result of unprecedented urbanization during the second half of the 20th century. The urban population is projected to increase to 68% by 2050, with most of the increase occurring in Asia and Africa. Population growth and increased energy consumption in urban areas lead to high levels of atmospheric pollutants that harm human health, cause regional haze, damage crops, contribute to climate change, and ultimately threaten the society’s sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 113 publications
3
90
0
1
Order By: Relevance
“…In this analysis, the satellite-model (total column) ratio was compared versus the observations-model ratio (in surface). al., , Molina L.T. et al, 2019).…”
Section: Comparisons Between Measured Data and Model Resultsmentioning
confidence: 99%
“…In this analysis, the satellite-model (total column) ratio was compared versus the observations-model ratio (in surface). al., , Molina L.T. et al, 2019).…”
Section: Comparisons Between Measured Data and Model Resultsmentioning
confidence: 99%
“…This study found that a special strategy is needed to explain the causal pathways that link the factors of population movement, increased urban activity, and its effects on aspects of human health. Fourth, a study was conducted by Molina, L.T [48], by analyzing the effect of population growth and increased energy consumption in urban areas. This study compares the policies implemented in the Metropolitan area of Mexico City and Singapore and offers air pollution management to protect public health and the environment.…”
Section: Review Theorymentioning
confidence: 99%
“…In relation with vehicular emission, Singapore provides a successful precedent with its policies. Singapore combines traffic management, promotion of public transport and regulatory policies to reduce the number of cars [25]. Policies such as road-pricing schemes, vehicle inspection and elimination of old cars can be considered to be implemented in Jakarta.…”
Section: Evaluating Datamentioning
confidence: 99%